2020
DOI: 10.3390/brainsci10080533
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical T1-Rho MRI Abnormalities in Juvenile-Onset Huntington’s Disease

Abstract: Huntington’s disease (HD) is a fatal neurodegenerative disease caused by the expansion of cytosine-adenine-guanine (CAG) repeats in the huntingtin gene. An increased CAG repeat length is associated with an earlier disease onset. About 5% of HD cases occur under the age of 21 years, which are classified as juvenile-onset Huntington’s disease (JOHD). Our study aims to measure subcortical metabolic abnormalities in JOHD participants. T1-Rho (T1ρ) MRI was used to compare brain regions of 13 JOHD participants and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Evidence from the Kids-HD study using resting-state functional magnetic resonance imaging (fMRI) adds to this picture. Striatal-cerebellar hyperconnectivity was observed across some connection pathways from age 6 to age 12, followed by hypoconnectivity in the years that followed through age 20 (Tereshchenko et al, 2020). This effect suggests an early compensatory increase in connectivity that gives way to reduced connectivity as children move into and through their teenage years.…”
Section: Childhood and Adolescencementioning
confidence: 94%
“…Evidence from the Kids-HD study using resting-state functional magnetic resonance imaging (fMRI) adds to this picture. Striatal-cerebellar hyperconnectivity was observed across some connection pathways from age 6 to age 12, followed by hypoconnectivity in the years that followed through age 20 (Tereshchenko et al, 2020). This effect suggests an early compensatory increase in connectivity that gives way to reduced connectivity as children move into and through their teenage years.…”
Section: Childhood and Adolescencementioning
confidence: 94%
“…9 Cross-sectional analyses have demonstrated that patients with JOHD have significant neurodegeneration in cortical and subcortical brain regions shortly after receiving a diagnosis of JOHD. 10,11 However, quantifying clear measures of longitudinal disease progression in JOHD is an imperative step in the planning and conduct of clinical trials in this population. This study aimed to evaluate longitudinal clinical and neuroimaging changes in a relatively large cohort of JOHD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the same cannot be said for patients with JOHD 9 . Cross‐sectional analyses have demonstrated that patients with JOHD have significant neurodegeneration in cortical and subcortical brain regions shortly after receiving a diagnosis of JOHD 10,11 . However, quantifying clear measures of longitudinal disease progression in JOHD is an imperative step in the planning and conduct of clinical trials in this population.…”
Section: Introductionmentioning
confidence: 99%